System Analysis and Design - Kumari, Naveen (Delhi : S.K. Kataria and Sons, 2015)
For undergraduate systems analysis and design courses. Kendall and Kendall's 'Systems Analysis and Design' is a human-centred book that concisely presents the latest systems development methods, tools, and techniques to students in an engaging and easy-to-understand manner.
Keywords: Systems Analysis; Systems Design; Systems programming